Special Characteristics of Culturing Mature Human Bladder Smooth Muscle Cells on Human Amniotic Membrane as a Suitable Matrix - Sharifiaghdas, Farzaneh; Moghadasali, Reza; Baharvand, Hossein; Hosseini-Moghaddam, Seyed Mohammadmehdi; Mahmoudnejad, Nastaran (Urology Journal, 2009)
Introduction: Our aim was to evaluate the natural behavior, growth pattern, morphology, and specific features of human bladder smooth muscle cells (HBSMCs) on two different matrixes, including human amniotic membrane (HAM) and collagen. Materials and Methods: The HBSMCs were obtained from 6 children with primary vesicoureteral reflux undergoing open antireflux surgery, and they were isolated from the anterior wall of the bladder. The specimens were cultured on a tissue culture plate of bovine dermal collagen serving as control and on decellularized HAM. Histological, transmission electron microscopy, and immunocytochemical examinations were done, thereafter.Results: On HAM, very few HBSMCs slowly migrated from explant tissue on the 7th day of culture. All the cells were placed at the same direction, and in some parts, formed multilayer. After 35 to 40 days, the confluency rate was 75% and the cells were orderly arranged. On collagen, cell migration from explant culture took place as rapidly as the 3rd to 4th day of culturing. On days 30 to 40, the confluency rate was 100%. Immunocytochemical staining was positive for anti-actin and antidesmin antibodies. On transmission electron microscopy, cell organelles of HBSMCs exhibited the same features of the natural smooth muscle cells. They were tightly attached to each other and the underlying layer basement membrane. Conclusion: A well-designed growth pattern of HBSMCs on HAM with abundant cell-to-cell adhesions encourages us to use it as a competent tissue for reconstruction of relatively damaged or diseased bladders. Undoubtedly, further clinical studies should be performed to replicate our results.